Application of Finger-Hold Relaxation Technique on Postoperative Pain Intensity in Laparotomy Patients: A Case Study in dr. Moewardi General Hospital, Surakarta - Auliasa Hanum Kayasa; Eska Dwi Prajayanti; Isti Wulandari (Al-Hijrah Indonesia, 2025)
Background: Effective postoperative pain management is essential to enhance recovery, reduce complications, and improve patient comfort following major abdominal surgery such as laparotomy. Non-pharmacological interventions offer safe adjuncts to conventional analgesia, particularly in resource-conscious or multimodal pain management settings. Objective: This study aimed to evaluate the effectiveness of the finger grip relaxation technique in reducing pain intensity among post-laparotomy patients. Methods: A descriptive case study was conducted with two female patients diagnosed with colon cancer who underwent elective laparotomy at Flamboyan 5 Ward, Dr. Moewardi General Hospital, Surakarta, Indonesia. Pain intensity was assessed using the Numeric Rating Scale (NRS; 0–10) before and after the intervention. The finger grip relaxation technique, a simple, self-administered method involving rhythmic gripping and releasing of the fingers, was applied once daily for three consecutive days, with each session lasting 20 minutes. Results: Both patients exhibited clinically meaningful reductions in pain intensity following the intervention. Patient A’s NRS score decreased from 4 to 2, and Patient S’s score declined from 6 to 3, indicating a shift from moderate to mild pain levels. No adverse effects were observed. Conclusion: The finger grip relaxation technique is a feasible, non-invasive, and low-cost adjunctive strategy for managing acute postoperative pain after laparotomy. These preliminary findings support the integration of this approach into multimodal pain management protocols. However, larger controlled trials are warranted to confirm efficacy, determine optimal dosing, and assess broader clinical applicability.